Intellectual entertainments : eight dialogues on mind, consciousness and thought - Hacker, P. M. S. (Peter Michael Stephan) (London : Anthem Press, 2019)
'Intellectual Entertainments' consists of eight dialogues on the nature of the mind and consciousness, thought and thinking, perceptual qualities and ownership of pain. Each dialogue has five participants, some living, some dead and some imaginary who represent different points of view. No philosophical knowledge is presupposed.
<Span data-sheets-value="{"1":2, "2":"Preface; Acknowledgements; Section 1 Two Dialogues on Mind and Body; Introduction; First Dialogue On the Nature of the Mind; Second Dialogue The Mind and the Body; Section 2 Two Dialogues on Consciousness; Introduction; Third Dialogue The Mystery of Consciousness; Fourth Dialogue Consciousness as Experience -- Consciousness as Life Itself; Section 3 A Dialogue on Secondary Qualities; Introduction; Fifth Dialogue On the Objectivity or Subjectivity of Secondary Qualities; Section 4 Two Dialogues on Thought; Introduction; Sixth Dialogue On the Nature of Thought; Seventh Dialogue Thought and Language; Section 5 A Dialogue on Ownership of Pain; Introduction; Eighth Dialogue Can You Have My Pain? Can Different People Have the Same Pain?; Index."}" data-sheets-userformat="{"2":769, "3":{"1":0}, "11":3, "12":0}">Preface; Acknowledgements; Section 1 Two Dialogues on Mind and Body; Introduction; First Dialogue On the Nature of the Mind; Second Dialogue The Mind and the Body; Section 2 Two Dialogues on Consciousness; Introduction; Third Dialogue The Mystery of Consciousness; Fourth Dialogue Consciousness as Experience -- Consciousness as Life Itself; Section 3 A Dialogue on Secondary Qualities; Introduction; Fifth Dialogue On the Objectivity or Subjectivity of Secondary Qualities; Section 4 Two Dialogues on Thought; Introduction; Sixth Dialogue On the Nature of Thought; Seventh Dialogue Thought and Language; Section 5 A Dialogue on Ownership of Pain; Introduction; Eighth Dialogue Can You Have My Pain? Can Different People Have the Same Pain?; Index.
Online resource; title from PDF title page (EBSCO, viewed October 23, 2019)
JSTOR
Keywords: Philosophical anthropology; Philosophy of mind; Thought and thinking; Thinking; Anthropologie philosophique; Philosophie de l'esprit.; Pensée.; philosophical anthropology; thinking; PHILOSOPHY -- General; Philosophical anthropology; Philosophy of mind; Thought and thinking